Analysis of different casting techniques on properties of preplaced aggregate concrete - Thanapol Rujjiradthitikan; Pennung Warnitchai; Thanakorn Pheeraphan; Punchet Thammarak; Raktipong Sahamitmongkol; Royal Thai Government Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2023)
From the literature review, increasing the amount of sand to binder can improve the flexural strength, and this thesis concerns the improvement of the flexural strength of preplaced aggregate concrete by increasing the sand content. However, an increase in the amount of sand per binder in the mix proportion results in a bad of the flow ability of the grout. Therefore, the introduction of techniques in preplaced aggregate concrete mixing to help increase the amount of sand in the mix proposal is possible. In this study, beginning with the prescreening test that are superplasticizer comparison between brand A and B, and the maximum od sand content that can added in each techniques. After the prescreen test, superplasticizer and maximum amount of sand to binder were selected. Then, the mix proportion designed. Finally, after experiment result getting, there lead to the analysis part on focusing the effect of the sand content in the mix proportion especially the flexural strength which is one of the objectives of this thesis
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Structural Engineering
Thesis (M. Eng.) - Asian Institute of Technology, 2023
Keywords: Aggregates (Building materials); Concrete -- Additives -- Testing